A critical evaluation of the aerobic capacity demands of elite male soccer players - Shalfawi, S. A. I.; Tjelta, L. I. (International Journal of Applied Sports Sciences, 2016)
The present review investigate whether aerobic capacity of elite male soccer players has changed over the past 30-40 years, and sought to establish an improved estimate of aerobic capacity based on results reported in the literature. A systematic review of manuscripts reporting the match distance covered and/or the VO2max of elite male soccer players was performed. Eighteen studies (published between 1967 and 2010) reporting the total distance covered and representing 14 countries (3,833 players), and 25 studies (published between 1975 and 2012) reporting VO2max and representing 22 countries (1,921 players) were selected for analysis. Little, if any, relationship existed between the mean match play distance covered/VO2max and the year of measurement/reporting. An improved estimate of the match play distance covered was calculated as 10,418 m with a pooled standard deviation of ± 933 m (95% confidence interval [CI] = 10,053 ? 10,783 m) and a maximum mean of 12,650 m and minimum of 8,638 m. In addition, the improved estimate of the VO2max was calculated as 59.38 mL/kg/min¹, with a pooled standard deviation of ± 3.74 mL?kg?¹?min?¹ (95% CI = 57.99 ? 60.78 mL?kg?¹?min?¹) and a maximum mean of 67.6 mL?kg?¹?min?¹, and a minimum of 52.1 mL?kg?¹?min?¹. The results suggest that distance covered and VO2max in elite male soccer players have been stable over the period from 1967 to 2012 and that aerobic metabolism is the major source of energy during the match. Thus, soccer players must possess a minimum aerobic capacity to cover the total match distances and to recover from high-intensity action.